Wacana Pengampunan Pajak: Kajian Kohesi dan Koherensi - ., Sifandi; Simpen, I Wayan; Putu Putra, Anak Agung (Humanis; Vol 22 No 3 (2018), 2018)
Entitled with “The Discourse of Tax Amnesty: The Study of Cohesion and Coherence” this research purpose is to know the instrument of cohesion and coherence which built the discourse of the tax amnesty. The teory used is the discourse teory which are cohesion mentioned by Halliday and R. Hasan (in Dewi, 2010:20) and coherence mentioned by Kridalaksana (in Mulyana, 2005:32). The method used in data collection is scrutinize method which completed by technique note. In data analysis process used agih method which method use the language as the determiner helped by lesap technique and replacement technique afterwards. Furthermore, informal and formal method used as the presentation process of analysis data result. In informal presentation use common words, while the formal presentation use sign and symbol. The data source which used as the analysis materials with total of 62 articles comes up from K ompas. C om issued at February and March 2017. There are some revelation obtained based on the analysis in discourse of the tax amnesty. Firstly, in the discourse of the tax amnesty dicovered that the instrument of cohesion out from grammatical (references, substitution, ellipsis, and conjunction) as well as lexical (repetition, synonym, antonym, collocation, and equivalence). Secondly, the coherence elements in the discourse of the tax amnesty are the causality relationship, instrument goal relationship, conclusion background relationship, leniency results relationship, parafrastis relationship, amplicative relationship, time additive (simultaneous and in sequence) relationship, non-time additives relationship, identification relationship, and spesific generic relationship.